(untitled) (Fiep Bulletin - online, 2014)
Introduction: The following proposal is a report of an interdisciplinary therapeutic method that sought to contribute to improving the health and interfere with the complaints and sufferings of women with fibromyalgia syndrome (FMS). Methodology: The methodology had the precepts of multiple references and interdisciplinary. These women were divided into groups of care. All treatment groups had a combination of medication, hydrotherapy, monitoring group with psychology and nutrition guidelines. The results were expressed both by qualitative analyzes as per quantitative. Conclusion: Women who received interdisciplinary and complementary therapy had significant improvements in both subjective and objectively his complaints of pain, gain energy, the reunion with themselves and their relationships, especially family. During the implementation of the program in the form of extension project , it could be said: 1) conventional physiotherapy does not produce favorable results, why not have a look multireferential about people who have FMS, about their potential health and thus, it is not articulating interdisciplinary; 2) symptoms and physical suffering is perpetuated when people are treated conventionally , because they do not understand what they are, which led them to forget the happiness, pleasure, desire to live, in short, which led them to become ill, and third. Emotional distress is arguably the generator of physical suffering and further exacerbates the physical symptoms.